Reliability and importance measures for a general consecutive-type system. Issue 1 (2nd January 2021) - Makri, Frosso S.; Psillakis, Zaharias M.
ABSTRACT: A general consecutive-type system, called m -consecutive- k, ℓ -out-of- n :F system, is considered. Such a system consists of n linearly or circularly ordered components and fails if and only if there are at least m ℓ -overlapping runs of k consecutive failed components. For systems with statistically independent components, the system reliability is obtained via recursive schemes and simulation. Reliability importance measures for system components are calculated and analyzed as well. Illustrative analytic and numerical examples demonstrate further the theoretical results.